2013
DOI: 10.1586/17474124.2013.848790
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and telomere dynamics: relevance to cancers of the GI tract

Abstract: Summary Aberrations in telomere length and telomere maintenance contribute to cancer development. In this article, we review basic principles of telomere length in normal and tumor tissue and the presence of the two main telomere maintenance pathways as they pertain to GI tract cancer. Peripheral blood telomeres are shorter in patients with many types of GI tract cancers. Telomere length in tumor DNA also appears to shorten early in cancer development. Tumor telomere shortening is often accompanied by telomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 161 publications
1
23
0
Order By: Relevance
“…They gradually shorten over time, by approximately 30–200 bp after each cycle of mitotic division [6]. Incomplete replication of linear DNA molecules and gradual shortening of telomere length lead to regulated cell senescence and apoptosis or cell death, a process that acts as a key mechanism in cancer development [7, 8]. While earlier observational studies reported that a shorter TL in white blood cells (WBC) was associated with an increased risk of various cancers [912], cumulative evidence has discovered that a longer TL is also problematic, as it was found to be associated with increased risk of lung cancer [1315], pancreatic cancer [16], renal cancer [17], and breast cancer [18].…”
Section: Introductionmentioning
confidence: 99%
“…They gradually shorten over time, by approximately 30–200 bp after each cycle of mitotic division [6]. Incomplete replication of linear DNA molecules and gradual shortening of telomere length lead to regulated cell senescence and apoptosis or cell death, a process that acts as a key mechanism in cancer development [7, 8]. While earlier observational studies reported that a shorter TL in white blood cells (WBC) was associated with an increased risk of various cancers [912], cumulative evidence has discovered that a longer TL is also problematic, as it was found to be associated with increased risk of lung cancer [1315], pancreatic cancer [16], renal cancer [17], and breast cancer [18].…”
Section: Introductionmentioning
confidence: 99%
“…As was expected, low expression of miR-34a has also been found to be important in GBC (82). Additionally, previous studies have demonstrated that altered telomere length may contribute to cancer development and progression (83). In a study by Jin et al, miR-34a levels and telomere length were evaluated in 77 gallbladder adenocarcinomas and 36 peritumoral tissues by RT-PCR (82).…”
Section: Tumor Suppressor Micrornasmentioning
confidence: 89%
“…In contrast to that of gastric cancer tissues, telomere length in the gastric mucosal tissues expressing GKN1 was longer (Figure 6B , 6D and 6E ). Normal somatic cells do not usually activate telomerase to counter telomere shortening, and the gastrointestinal epithelium is characterized by a very high cellular turnover rate, which leads to renewal of the epithelium every 3–5 days [ 10 , 37 ]. The results of our study present for the first time that GKN1 may play a role in telomere maintenance by inhibiting c-myc-induced telomerase activation in gastric epithelial cells and that loss of GKN1 expression in gastric cancer cells may activate telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in telomere maintenance contribute to the initiation of genomic instability during carcinogenesis, including gastric cancer [ 8 , 9 ]. Telomere maintenance in cancer cells is often accompanied by activated telomerase to protect genetically damaged DNA from normal cell senescence or apoptosis [ 10 ]. However, little is known about telomere maintenance in gastric mucosal epithelial cells and its contribution to gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%